Influence of Empirical and Dynamic Periods on the Seismic Responses of Reinforced Concrete Buildings Braced by L-Shaped Shear Walls - Mohamed Khelladi; Smain Benyamina; Salem Merabti (The Journal of Engineering and Exact Sciences)
The Algerian Seismic Regulation of 1999, version 2003 (RPA99/v2003), presents ambiguities and a lack of thorough explanations in certain articles, which has led to a diversity of readings and interpretations among various stakeholders in the field, particularly the control offices. This situation has caused significant disagreements, especially during the approval of civil engineering files, thus resulting in a negative impact on project progress. To ensure adequate seismic protection of civil engineering structures, this work aims to unify the interpretations of certain passages of the regulation, with a particular emphasis on verifying the fundamental period of the structure, the shear forces at the base, and inter-story displacements using seismic calculation methods prescribed by the RPA. The comparative study demonstrates that no correlation between the period determined by the equivalent static method and that calculated by the spectral modal analysis method has been observed. This justifies the conclusion that adjusting between the empirical period and the dynamic period is not necessary.